Leaf spots of Manhattan - Swingle, Dean Brett (My University, 1900)
Introduction: The term “leaf spot” is one that is not easily defined, but in this work it shall be made to include all those parasitic fungi, belonging mostly, to the group Pyrenomycetes, whose conidial stage only is known (and a few also whose complete life history has been worked out) and which form more or less clearly defined spots on the leaves of the higher plants. As only the conidial stage is known it is, as yet, impossible in most cases, to say exactly where they belong in relation to other fungi. The conidia are to facilitate the spread of the fungi during the summer; and it is supposed that there is, for each species, another stage growing either on the same, or on another host plant, in which flask shaped perithecia containing asci, are born later in the season for perpetuating the species over winter. In some cases this has been proven to be true; but for the majority of the species the truth or falsity of this theory is yet to be determined. That the different stages may be more clearly understood, we will take as an example the strawberry leaf spot (Sphaerella Fragariae) which is typical of the group, and of which we have now the complete life history.
Citation: Swingle, Dean Brett. Leaf spots of Manhattan. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Fungi; Pyrenomycetes; Leaf Spot; Sphaerella Fragariae; Theses